Pengaruh Corporate Social responsibility, Capital Intensity, dan Transfer Pricing terhadap Tax Avoidance - Kamila, Sahla; Khasanah, Uswatun; Nuryati, Tutty (Rifa'Institute, 2023)
This study aims to obtain empirical evidence about the effect of corporate social responsibility, capital intensity, and transfer pricing on tax avoidance. This study uses a data sample of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2021 period. The number of companies used as samples were 14 companies with observations for 4 years using purposive sampling method. The data analysis technique used is multiple linear regression The results of multiple linear regression testing show that the corporate social responsibility and capital intensity variables have a negative effect on tax avoidance, while the transfer pricing variable has a positive effect on tax avoidance.